THE HYPERSEMIOTICS OF JAVANESE PROVERBS IN APPRECIATING THE MORNING AND EVENING TIME IN THE SOCIETY OF PASURUAN CITY - Suwadi, Suwadi (Elite Laboratory Jurusan Sastra Inggris Universitas Bangka Belitung, 2025)
This study focuses on how the people of Pasuruan City apply the values of Javanese pitutur in appreciating the morning and evening as integral parts of daily life. Pitutur Jawa, as a form of local wisdom, not only serves as a moral guide but also influences the habits and behavioral patterns of the community. To understand how the meanings embedded in these pitutur are applied in real life, this research employs a hypersemiotics approach, allowing for an in-depth exploration of signs and symbols within the culture of Pasuruan society. The use of hypersemiotics in this study aims to uncover the meanings behind pitutur expressions related to morning and evening time. By utilizing qualitative methods and descriptive analysis, this research collects data through direct observation and interviews with local communities, including cultural figures and residents who uphold the tradition of Javanese pitutur. The collected data is then analyzed to reveal how the people of Pasuruan City interpret and implement these pitutur values in their lives. The findings indicate that the people of Pasuruan City have a deep understanding of the significance of morning and evening in their daily lives. The morning is perceived as a time to be utilized for productivity and discipline. They believe that the morning is the best time to start work with enthusiasm, as reflected in the pitutur